Efficient Photocatalytic Degradation of Rhodamine B Dye by Aligned Arrays of Self-Assembled Hydrogen Titanate Nanotubes. (15th April 2014) - Chatterjee, Sriparna; Tyagi, Avesh K.; Ayyub, Pushan
Abstract : We show that an aligned array of hydrothermally grown, multiwalled hydrogen titanate (H2 Ti3 O7 ) nanotubes—anchored to both faces of a metallic Ti foil—acts as an efficient photocatalyst. We studied the degradation of rhodamine B dye in the presence of the nanostructured photocatalyst under UV irradiation, by monitoring the optical absorption of the dye. Rhodamine B was chosen as a representative—and particularly harmful—industrial pollutant dye. The inner and outer diameters of the H2 Ti3 O7 nanotubes were 5 nm and 10 nm, respectively. The nanotube array catalyst is recyclable and structurally stable. Most importantly, it shows comparable or higher photodecomposition rate constant than those of both H2 Ti3 O7 nanotube powder and P-25 (Degussa). The enhanced photocatalytic performance may be ascribed to the nanotube array having a superhydrophilic surface with a high accessible surface area.